Determination of Serum Vitamin D3 Level by High Performance Liquid Chromatography (HPLC) in Patients with Coronary Artery Ectasia - Babat, Naci; Türkmen, Yusuf (Cardiology and Cardiovascular Medicine, 2020)
Background and Objectives: The net clinical effect of vitamin D on atherosclerosis and therefore coronary arteria ectasia (CEA) is controversial. While many trials have showed the favorable effects of vitamin-D others were related with negative outcomes and the exact levels of serum vitamin-D were not consistent with clinical outcomes. So therefore, we aimed to measure the levels of vitamin-D by HPLC technique which is better than conventional spectrophotometric methods. Methods: A total of 202 patients were enrolled to our study and 102 of them were in patient group. They have diagnosed with CEA by angiographically and the level of vitamin-D was measured by High Performance Liquid Chromatography (HPLC) technique both in the patients of control and study group. Results: There was no statistically meaningful difference between groups according to the basic but the serum levels of vitamin-D were lower in patients with CEA with a mean value of 20.5 ng/ml and the average amount of serum vitamin-D was 54.6 ng/ml in control subjects (p<0.001). Conclusions: The serum levels of vitamin-D were detected as clearly lower by HPLC technique in patients with CEA and it has proved one more time the relation of lower levels of serum vitamin-D and CEA. At the same time, the method showed extremely high or totally normal values of vitamin-D levels in patients without CEA which has been not showed previous trials. Also, HPLC may yield more accurate results of serum vitamin-D than other spectrophotometric measuring techniques particularly in normal individuals.